Circular economy‐based new products and company performance: The role of stakeholders and Industry 4.0 technologies. (27th September 2021) - Pinheiro, Marco Antonio Paula; Jugend, Daniel; Lopes de Sousa Jabbour, Ana Beatriz; Chiappetta Jabbour, Charbel Jose; Latan, Hengky
Abstract: While the circular economy (CE) attracts attention from scholars and practitioners, the concept has been challenged by claims that the CE may be seen as a vague concept, or a new label for old green management practices. We propose a new approach to study the effects of the CE on company performance: circular product design (CPD). Consequently, this work investigates how Industry 4.0 technologies and stakeholder pressure influence CPD and, in turn, impact on company performance. Data were obtained from firms which develop products in the electric–electronic and equipment (EEE) sectors in Brazil. Our research results indicate that (i) the application of Industry 4.0 technologies favors CPD, in particular artificial intelligence and big data analytics; (ii) pressure from stakeholders can encourage the adoption of circular strategies, specially from suppliers because they are responsible for developing and delivering smart components; and (iii) although the literature may be seen as controversial, there is a positive relationship with regard to the impacts of CE adoption on market performance. Among its main implications, the article also suggests a set of design strategies oriented towards the development of products for the CE.